ICMS Ecológico: Possibilities of support for the Urban Green Areas System in the building of healthier cities - Silva, Matheus Maramaldo Andrade; Bezerra, Maria do Carmo Lima (Electronic Journal "Fórum Ambiental da Alta Paulista", 2021)
The Urban Green Areas System (UGAS) performs relevant functions for the quality of life by making cities healthier, which has become even more necessary in the current period of pandemic. However, even with these benefits, the practice of urban management indicates difficulties not only in the implementation, but also in the maintenance of the UGAS. One of the aspects that may explain the challenge of implementing and maintaining green areas in cities is the absence of regulatory instruments and financial incentives that support this system. In this line, in order to contribute to this discussion, one of the instruments that proved to be effective in environmental management will be studied, in this case for the creation and implementation of Conservation Units: the “ICMS Ecológico”. This article will study the characteristics of the UGAS associated with ecological and urban functions; the logic of adopting the “ICMS Ecológico” and will seek to define criteria that can be used for the implementation of a UGAS that prioritizes ecosystem thinking associated with the function of urban health. We started with the discussion about the mechanisms for adopting the “ICMS Ecológico” and followed the analysis of the standards established in the states for its application. As a result, it was found that there are similarities that can be applied to an implementation in the urban green area systems, which allowed the recommendation of criteria that can be used as a reference for the application of the “ICMS Ecológico” to support the UGAS and the promotion of healthier cities.